The Effect of Feedback and Motivation on Service Ability in Junior Tennis Athletes in West Sumatera - Suci Nanda Sari; Juana Wangsa Putri (Program Pascasarjana Universitas Negeri Jakarta, 2022)
This study aims to test the influence of Feedback giving and motivation on the service ability of junior tennis athletes in West Sumatra. Thirty athletes were randomly divided into four groups (Direct Feedback high motivation n = 10), (Direct Feedback high motivation n = 10) and (Indirect Feedback high motivation n = 10), (Indirect Feedback high motivation n = 10) assigned to complete service training interventions with a feedback approach for 6 weeks, 3 days/week. Serviceability test using Hewwit tennis test. The findings in this study show that there is a significant positive influence from giving feedback in the direct feedback group with high motivation to improve the service ability of West Sumatra junior tennis athletes. obtained the average score of service ability of the high motivation group taught with direct feedback is 28.40 and the low motivation group is 22.00 For the average score of service ability of the high motivation group taught with indirect feedback 23.70 and the low motivation group is 23.80.